Self- Cleaning Materials: Review of Recent Progress and Innovations - Nyong, Aniedi; Peter, Idara; Awaka-Ama, Joachim; Udoh, Godwin (Researchers Journal of Science and Technology, 2021)
This paper is a review of some of the trends in the theoretical conception and development of self-cleaning materials for various applications. This review is significant as it highlights briefly the various research activities in the area of self-cleaning materials. Beyond the Wenzel, Cassie-Baxter and Young’s Models that are used in theoretically examining the concept of self-cleaning, there is advancement of modelling and simulation of contact angles behaviour to include the effect of gravitational forces. Furthermore, research trends in three (3) different areas, namely; self-cleaning glasses, self-cleaning fabrics and self-cleaning cements have been discussed in some details. It has been noted that researches have focused on the use of photocatalyst, mainly TiO2 and SiO2, to generate self-cleaning surfaces that are capable of photodegrading organic matter. These photo-catalysts are added in-situ to the materials or coated on to the materials’ surfaces. Different methods of coating of these photocatalysts on to the surfaces of the materials have been developed. Some of these coating methods that have seen great interest recently are the pad-dry cure and sol-gel coating methods